Pertussis: Resurgence of a forgotten entity - Mukesh Kumar Jain; Sibabratta Patnaik; Bandya Sahoo; Reshmi Mishra (Wolters Kluwer Medknow Publications, 2020)
Pertussis is a serious and life-threatening infection of infancy. Recurrent apnea with a paroxysm of cough is the early clue for its diagnosis. The rate of pertussis increased worldwide with the occurrence of regular outbreaks globally, including India. The resurgence of pertussis is multifactorial, and it includes antigenic shifts in bacteria, decreasing vaccine immunity, reduced duration of protection by acellular pertussis vaccine, and improved method of surveillance and diagnosis. Family members, especially mothers and siblings, are an important source of pertussis transmission to vulnerable infants. Maternal vaccination for pertussis during pregnancy should be done as many cases of infantile pertussis was found before primary immunization. A 45 days infants admitted to the pediatric intensive care unit with recurrent apnea and bradycardia, require prolonged mechanical ventilation with intense cardiorespiratory monitoring. Real-time polymerase chain reaction of the nasopharyngeal swab for pertussis was positive. Successfully discharged after a long course of hospitalization.